Localized Morphological Modulation of Ultrathin Magnetic Nanosheets via a Strategically Designed Reduction Approach - Liu, Xianyuan; Wang, Xianghua; Lu, Xianyong; Jiang, Lei (Small (Weinheim an der Bergstrasse, Germany), 2025)
2D inorganic nanomaterials have attracted considerable research interest owing to their exceptional physical and chemical properties. Nonetheless, achieving precise control over the morphology of 2D nanomaterials presents a significant challenge, primarily due to their elevated surface energy and the stringent requirements for growth control. In this study, a designed reduction technique is employed to finely tune the morphology of 2D nanosheets, with iron salts serving as morphology‐directing agents. Al‐doped α‐Fe2O3 nanosheets are synthesized through a solvothermal process and subsequently reduced to Al‐doped Fe3O4 nanosheets, characterized by distinctive sawtooth‐like edges. The incorporation of iron salts facilitates atomic rearrangement within the iron oxide lattice, wherein rapid atomic migration induces defects along the crystal facets, resulting in unique morphologies. Furthermore, the doping of aluminum elements and the resultant Fe3O4 significantly enhance the electromagnetic properties of the nanosheets, yielding exceptional electromagnetic wave absorption performance. Notably, a remarkable minimum reflection loss (RLmin) of −66.1 dB is achieved at a thickness of 4.0 mm, with an effective absorption bandwidth (RL ≤ −10 dB) extending up to 3.9 GHz. This controlled reduction strategy presents a promising pathway for tailoring the morphology of 2D nanomaterials and optimizing their performance in electromagnetic wave absorption applications. A controlled reduction method is reported to regulate the morphology of 2D magnetic nanosheets. Through precise control of reaction conditions, nanosheets with unique sawtooth‐like edges are obtained. The synergistic effect of element doping and morphology control results in excellent electromagnetic wave absorption properties. This provides a new approach for the morphological control of 2D nanomaterials and broadens their application field.